Motor Unit Action Potential Clustering—Theoretical Consideration for Muscle Activation during a Motor Task - Asmussen, Michael J.; von Tscharner, Vinzenz; Nigg, Benno M. (Frontiers in Human Neuroscience, 2018)
During dynamic or sustained isometric contractions, bursts of muscle activity appear in the electromyography signal. Theoretically, these bursts of activity likely occur because motor units are constrained to fire temporally close to one another and thus the impulses are “clustered” with short delays to elicit bursts of muscle activity. The purpose of this study was to investigate whether a sequence comprised of “clustered” motor unit action potentials (MUAP) can explain spectral and amplitude changes of the EMG during a simulated motor task. To this end, we modelled two EMG signals, whereby a single MUAP was either convolved with a randomly distributed impulse train (EMG-rand) or a “clustered” sequence of impulses (EMG-clust). The clustering occurred in windows lasting 1 to 100 ms. A final mixed signal of EMG-clust and EMG-rand, with ratios (1:1 to 1:10), was also modelled. A ratio of 1:1 would indicate that 50% of MUAP were randomly distributed, while 50% of “clustered” MUAP occurred in a given time window (1 to 100 ms). The results of the model showed that clustering MUAP caused a downshift in the mean power frequency (i.e., ~30 Hz) with the largest shift occurring with a cluster window of 10ms. The mean frequency shift was largest when the ratio of EMG-clust to EMG-rand was high. Further, the clustering of MUAP also caused a substantial increase in the amplitude of the EMG signal. This model potentially explains an activation pattern that changes the EMG spectra during a motor task and thus, a potential activation pattern of muscles observed experimentally. Changes in EMG measurements during fatiguing conditions are typically attributed to slowing of conduction velocity but could, per this model, also result from changes of the clustering of MUAP. Based on our model, researchers moving forward should consider how MUAP clustering influences EMG spectral and amplitude measurements.